Intrinsic Motivation and Cultural Diversity in Increasing Knowledge Sharing Intention with Employee Engagement as an Intervening Variable: Motivasi Intrinsik dan Cultural Diversity dalam Meningkatkan Knowledge Sharing Intention dengan Employee Engagement sebagai Variabel Intervening - Nofyaningrum, Mya Aditya; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2021)
This study aims to determine the Intrinsic Motivation and Cultural Diversity in increasing Knowledge Sharing Intention with Employee Engagement as an Intervening Variable in the owners of IKM KAMPUNG PIA GEMPOL PASURUAN. The population used is all owners of IKM KAMPUNG PIA GEMPOL PASURUAN, totaling 100 people, and in this study 100 people were sampled. The sampling technique used in this study was a saturated sample. Data collection is done through the distribution of questionnaires. To test the hypothesis used multiple linear regression analysis, multiple correlation coefficient (R), multiple determination coefficient (R2), classical assumption test, F test and t test with the help of SPSS statistics 18.0, as well as validity and reliability tests. The results of the validity test and reliability test showed that all items in the questionnaire were valid and reliable because the value of rcount was greater than the value of rtable. The results of this study proved that intrinsic motivation (X1) affects knowledge sharing intention (Y), cultural diversity (X2) also has an effect on knowledge sharing intention (Y), employee engagement (Z) has an effect on knowledge sharing intention (Y), besides that intrinsic motives (X1), cultural diversity (X2), and employee engagement (Z) have direct and indirect effects on knowledge sharing intention (Y).